LEVELS OF HORMON ESTROGEN IN BALI CATTLE DURING PUBERTY - Prananda, Herdi Wahyu Adi; Laksmi, Desak Nyoman Dewi Indira; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana, 2022)
Bali cattle is one of the most important native cattle in Indonesia. There is one measure of reproductive efficiency. The achievement of early age of puberty in accordance with its genetic potential is important to achieve optimum reproductive performance and provide increase in productivity. One of the things that affects the appearance of puberty is the amount of estrogen in the blood serum. The purpose of this study was to determine the levels of estrogen in cattle blood serum. The study was conducted by recording the age first and then taking blood in cattle that had signs of puberty and then carried out checking hormone levels using the ELISA method. The results showed that the average age of puberty was 21.44 months and the average estrogen level at puberty was 84.75 ng / ml. Testing with correlation and regression tests showed a close relationship between age and estrogen levels at puberty with a correlation coefficient of r = 0.798.